FAKTOR-FAKTOR PENYEBAB PERILAKU MELUKAI-DIRI PADA REMAJA PEREMPUAN - Bernardus Khrisma Wibisono; Elly Yuliandari Gunatirin (Perpustakaan Universitas Surabaya, 2018)
Self-injury is a non-suicidal way to relieve emotional pain and distress by deliberately hurting their bodies. There are external and internal factors causing self-injurious behavior on adolescents. The external factor is an authoritarian parenting style, and the internal one is the trait of neuroticism. The study has an interpretive perspectives and case study as its approach. The study also has a qualitative approach by interviewing and observing as the methods to collect data. The subjects of this study are around 17-20 year-female adolescents which were committed to self-harm. Also, this study has theory triangulation and methodical triangulation for the credibility of this research. The result of this study is that external factor of self-injurious behavior is social pressure from parents, family, and also other relatives. Its internal factors are loss, low self-esteem, and trauma. The main risk factors are the situations to family disorganization (affair and divorce). These factors are supported with authoritarian parenting style (physical punishments and verbal violence) and neuroticism (of pride and sosial-acceptance). Its protective factors are the reconciliation with parents and self-motivation, also the support of social control.